Performance optimization of cloud storage in access control of Ciphertext Policy Attribute-based Encryption - Mohd Satar, Siti Dhalila (2023)
In this research, we address the critical need for enhanced cloud computing security and performance by developing an access control framework. This framework integrates an Ciphertext Policy Attribute-based Encryption (CP-ABE) with mechanisms aimed at optimizing the performance of access policy hiding process while strengthening the users’ privacy and streamlining data access processes. Specifically, we introduce a modified CP-ABE model that incorporates Access Policy Hiding (APH), the Tokenization Identifier (TId) technique, and Priority Task Scheduling (PriTask) to tackle prevalent challenges in cloud storage systems. The core of our proposal lies in the implementation of APH to optimize the performance of concealing access policies, a move that significantly curtails potential privacy breaches by preventing unauthorized entities from gleaning attribute information from access policies. This strategy not only enhances user privacy but also contributes to a reduction in processing time which increase the performance of CP-ABE. Concurrently, the TId technique is employed to mitigate data redundancy within files. This method ensures a more compact plaintext format, thereby reducing the storage cost, optimizing the performance of encryption and minimizing the demands on cloud storage space. To address the inefficiencies during peak traffic periods, our framework incorporates the PriTask module, a scheduling mechanism designed to prioritize decryption tasks. This optimization reduces response times and average delay time, ensuring swift and reliable access to encrypted data stored in the cloud. Our experimental setup utilized a CP-ABE simulation tool, developed using Java and leveraging the CP-ABE open-source library, with foundational support from the Java pairing-based cryptography (JPBC) library. The empirical evidence highlights the efficacy of our approach, revealing a 10.6% improvement in average processing time—679 milliseconds compared to the benchmark of 791 milliseconds. Moreover, our method achieved a nearly 5% reduction in storage cost relative to standard models. The introduction of PriTask notably expedited decryption processes and alleviated response times, further underscoring the performance advantages of our modified CP-ABE framework. In summary, the integration of APH, TId, and PriTask within a modified CP-ABE schema presents a robust solution to the dual challenges of cloud security and data access efficiency. This study not only demonstrates the feasibility of enhancing cloud data management through innovative encryption and scheduling techniques but also sets the stage for future research avenues, including advanced attribute management, multi-tiered access control, and scalability enhancements. Our findings contribute to the ongoing evolution of secure and efficient cloud computing paradigms.